Distinct pathways control recruitment and maintenance of myosin II at the cleavage furrow during cytokinesis. - Dean, S.O.; Rogers, S.L.; Stuurman, N.; Vale, R.D.; Spudich, J.A. (Proceedings of the National Academy of Sciences of the United States of America, 2005)
The correct localization of myosin II to the equatorial cortex is crucial for proper cell division. Here, we examine a collection of genes that cause defects in cytokinesis and reveal with live cell imaging two distinct phases of myosin II localization. Three genes in the rho1 signaling pathway, pebble (a Rho guanidine nucleotide exchange factor), rho1, and rho kinase, are required for the initial recruitment of myosin II to the equatorial cortex. This initial localization mechanism does not require F-actin or the two components of the centralspindlin complex, the mitotic kinesin pavarotti/MKLP1 and racGAP50c/CYK-4. However, F-actin, the centralspindlin complex, formin (diaphanous), and profilin (chickadee) are required to stably maintain myosin II at the furrow. In the absence of these latter genes, myosin II delocalizes from the equatorial cortex and undergoes highly dynamic appearances and disappearances around the entire cell cortex, sometimes associated with abnormal contractions or blebbing. Our findings support a model in which a rho kinase-dependent event, possibly myosin II regulatory light chain phosphorylation, is required for the initial recruitment to the furrow, whereas the assembly of parallel, unbranched actin filaments, generated by formin-mediated actin nucleation, is required for maintaining myosin II exclusively at the equatorial cortex.